If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7a + -2 = 10 + 7a + 4a Reorder the terms: -2 + 7a = 10 + 7a + 4a Combine like terms: 7a + 4a = 11a -2 + 7a = 10 + 11a Solving -2 + 7a = 10 + 11a Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-11a' to each side of the equation. -2 + 7a + -11a = 10 + 11a + -11a Combine like terms: 7a + -11a = -4a -2 + -4a = 10 + 11a + -11a Combine like terms: 11a + -11a = 0 -2 + -4a = 10 + 0 -2 + -4a = 10 Add '2' to each side of the equation. -2 + 2 + -4a = 10 + 2 Combine like terms: -2 + 2 = 0 0 + -4a = 10 + 2 -4a = 10 + 2 Combine like terms: 10 + 2 = 12 -4a = 12 Divide each side by '-4'. a = -3 Simplifying a = -3
| 3/5x-2/3 | | 3/5x-2/5 | | -2+5v=9v+10 | | 12-9b=6-8b | | 2u+8u-5u= | | An=1/27*3^n-1 | | 1-8x=-7-6x | | 3/5x-2/5=3/10 | | -(3x-3)=-6-2x | | 17-9n=1-7n | | 4/3=v/8 | | 2x-5x=-5-2x | | 3r-6=2r-2r | | 0=3b+21 | | 1+3p=-4p+15 | | -18+7m=m-6-6 | | Y/3-3=11 | | 6n-14=4n+16 | | k-6=m+18 | | 3x=y+16 | | 3(-2x+1)=7(-3x-6) | | 7(5-2a)=5(-3a+1) | | 3x-5(x-4)=-2+3x-8 | | 8-5p+4P=5+2P-9 | | 6xln(1+x)-x=0 | | -3(7x+6)=-(6x+3) | | (2x)+(4y)=154 | | 11(68x-70)=900 | | 2v-20=10-v | | 1.23+x=5.47 | | -5x+7x=5x+9 | | 3y+5y+7y= |